Structural Sexism and Health in the United States: A New Perspective on Health Inequality and the Gender System - Homan, Patricia (American Sociological Review, 2019)
In this article, I build a new line of health inequality research that parallels the emerging structural racism literature. I develop theory and measurement for the concept of structural sexism and examine its relationship to health outcomes. Consistent with contemporary theories of gender as a multilevel social system, I conceptualize and measure structural sexism as systematic gender inequality at the macro level (U.S. state), meso level (marital dyad), and micro level (individual). I use U.S. state-level administrative data linked to geocoded data from the NLSY79, as well as measures of inter-spousal inequality and individual views on women’s roles as predictors of physical health outcomes in random-effects models for men and women. Results show that among women, exposure to more sexism at the macro and meso levels is associated with more chronic conditions, worse self-rated health, and worse physical functioning. Among men, macro-level structural sexism is also associated with worse health. However, greater meso-level structural sexism is associated with better health among men. At the micro level, internalized sexism is not related to physical health among either women or men. I close by outlining how future research on gender inequality and health can be furthered using a structural sexism perspective.